2015
DOI: 10.1016/j.jsbmb.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of epithelial ovarian cancer invasion into the omentum by 1α,25-dihydroxyvitamin D3 and its receptor

Abstract: Epithelial ovarian cancer (EOC) is the leading cause of gynecological cancer death in women, mainly because it has spread to intraperitoneal tissues such as the omentum in the peritoneal cavity by the time of diagnosis. In the present study, we established in vitro assays, ex vivo omental organ culture system and syngeneic animal tumor models using wild type (WT) and vitamin D receptor (VDR) null mice to investigate the effects of 1α,25-dihydroxyvitamin D3 (1,25D3) and VDR on EOC invasion. Treatment of human E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…At 14 days after i.p. injection, tumor infiltration first appeared in the omentum, which is a tissue attached to the greater curvature of the stomach and is the most common site for EOC metastatic spread [35] . As the disease progressed, a greater extent of the omentum was invaded by cancer cells (Fig.…”
Section: Characterization Of the Intraperitoneal Injection Ovarian Camentioning
confidence: 99%
See 2 more Smart Citations
“…At 14 days after i.p. injection, tumor infiltration first appeared in the omentum, which is a tissue attached to the greater curvature of the stomach and is the most common site for EOC metastatic spread [35] . As the disease progressed, a greater extent of the omentum was invaded by cancer cells (Fig.…”
Section: Characterization Of the Intraperitoneal Injection Ovarian Camentioning
confidence: 99%
“…This indicated that the urine proteins could show a significant immune response on the 14th day after the injection of tumor cells. In 80% of EOC patients, the cancer has usually spread to the omentum by the time of diagnosis [35] . In the pathology findings of our study, the omentum was first invaded by on day 14 in the model.…”
Section: Nutu-19 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Omentum was one of the organs most commonly involved in SOI metastasis, while omentum metastasis was rarely observed in COI. As it is understood that the omentum is the main target organ of ovarian cancer metastasis, up to 80% of epithelial ovarian cancer patients are found to have omentum metastasis when diagnosed (34,35). This suggests that the biological characteristics of cancer cells in the SOI model are more closely related to clinical disease, thus SOI is more clinically relevant.…”
Section: Organs -----------------------------------------------------mentioning
confidence: 99%
“…Further analyses have demonstrated that 1,25D3 induces microRNA target genes to decrease telomerase expression for cell death induction [10, 11] and to inhibit leptin and estrogen-induced tumor growth [12], suggesting that 1,25D3 has an important role in cutting down obesity-associated cancer risks in women [13]. More recent studies have shown that ovarian cancer invasion is suppressed by 1,25D3 through the cooperative actions of epithelial and stromal VDR [14]. Overall, these studies project VDR as a new therapeutic target for ovarian cancer intervention.…”
Section: Introductionmentioning
confidence: 99%